FATIGUE STRENGTH DEGRADATION OF THERMOMECHANICALLY ROLLED HIGH STRENGTH STEELS WELDS - Klejch, Filip; Schmidová, Eva (TANGER, spol. s r.o., 2021)
The good weldability of thermomechanically rolled high-strength steels is vital for contemporary steel structures. Full utilization of their capacity requires detailed knowledge and quantification of all processes that are involved by the heat-deformation cycle during welding. As good cold-formability is one of their promoted capabilities, residual stress gradient after forming to particular profile has the non-negligible effect on the dynamic resistance of welded joints.In this study, the dynamically stressed structural unit made of ALFORM 700M steel was investigated, where the initiation of fatigue damage during experimental test in connection with the degrading effect of welding was determined. Invoked processes are evaluated using structural analyzes. The heterogeneity of mechanical parameters is expressed by the local yield strength measured by the indentation method. Fractographic analysis of the initiation process and individual stages of fracture development reflects the influence of both welding and the initial quality of the steel.An important role of the residual stress of the formed profile is found out, leading to a limited extent to the delamination of the material during welding and thus decisively affects the fatigue resistance.
DEGRADACE ÚNAVOVÉ PEVNSOTI SVARU TERMOMECHANICKY VÁLCOVANÝCH VYSOKOPEVNÝCH OCELÍ
Keywords: high strength steels; thermomechanically rolled steels; delamination of rolled profile; weldability; indentation; vysokopevnostní oceli; termomechanicky válcované oceli; delaminace válcovaného profilu; svařitelnost; indentace